68Ga-PSMA PET/CT in patients with biochemical recurrence of prostate cancer: a prospective, 2-center study - Zacho, Helle Damgaard; Nielsen, Julie; Dettmann, Katja; Haberkorn, Uwe; Langkilde, Niels; Jensen, Jørgen; Petersen, Lars (Clinical nuclear medicine, 2018)
Purpose of the ReportThe aim of this study was to prospectively investigate the detection rate of 68Ga-PSMA PET/CT in biochemical recurrence (BCR) of prostate cancer and its impact on patient management.Materials and MethodsPatients with BCR after curatively intended treatment of prostate cancer wer